A Two Generation of Familial Adenomatous Polyposis - Lily Chandrawati; I Dewa Nyoman Wibawa (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Familial adenomatous polyposis (FAP) is a part of genetic polyposis syndrome which is caused by germline mutation in the adenomatous polyposis coli (APC) gene located in chromosome 5q21. The pathognomonic features is formation of hundreds to thousands of colorectal adenoma in late childhood and increase in size and number during adolescence. If left untreated, almost 100% patients will develop colorectal cancer by the age 50 years. We present a case of 26 year old male who complain of rectal bleeding, diarrhea, abdominal bloating, and has multiple polyps on colonoscopic finding. Two years ago, his father was diagnosed with polyposis coli and transverse colon adenocarcinoma. The patient was planned for preventive total colectomy. In conclussion, surgery remains the cornerstone treatment of FAP and surveillance program for early detection of cancer for all family member is very important to reduce colorectal cancer-related mortality.